Demoniczna transcendencja. Motyw faustowski w „Lśnieniu” Stanleya Kubricka - Kościelski, Kamil (Przestrzenie Teorii, 2013)
The interrelationship between literature and cinema is usually reduced merely to the connection between a book and its screen adaptation. Thus, a great many of the viewers of Stanley Kubrick’s The Shining would analyze its relation and fidelity to Stephen King’s novel. The reasoning presented in this essay stands in opposition to this tendency because various minor details of a movie may refer to other literary texts as well. In addition, a link to other works of art is often more meaningful and relevant than a reference to a book which was the basis of an adaptation. Therefore, it can be demonstrated that Kubrick alludes to Johann Wolfgang’s Faust in a variety of ways in The Shining. The comparison of the movie’s protagonist with the eponymous character of the play makes it easier to comprehend the cinematic character’s complex personality. This explains the content of The Shining even though the plot is based upon another literary text.